Combined Chemo-Anti-Inflammatory Prodrugs and Nanoparticles - Pathak, Rakesh K.; Dhar, Shanta (Synlett, 2016)
Combining multiple drugs in one platform has the ability to override the limitations of singly administered therapeutic and may provide potential alternative treatment options for aggressive prostate cancer resistant to conventional chemotherapy. For in vivo applications, combination therapeutics should be engineered to include nanoparticles for efficacious delivery. Here, we discuss the aspects of combining chemotherapy with anti-inflammatory drugs for metastatic castration resistant prostate cancer. We highlight the concept of combining cisplatin and Aspirin in a single platinum(IV) prodrug for efficacious in vitro biological actions. These two drugs were further incorporated in an engineered biodegradable polymer, which can self-assemble in the presence of a block copolymer to controlled-release nanoparticles to deliver multiple therapeutics in a predefined ratio.1 Introduction2 Chemo-Anti-inflammatory Approaches for Chemo-Resistant Prostate Cancer: Challenges and Opportunities3 Chemo-Anti-inflammatory Platinum(IV) Prodrugs4 Polymeric Nanoparticle for Co-delivery of Cisplatin and Aspirin5 Future Perspectives
Keywords: combination therapy; Platin-A; cisplatin; Aspirin; polymeric nanoparticles; inflammation; cancer